Geothermal Energy For Power Generation(GEPG) - Mohd.Saifful Izzuan Bin Ishak, Mohd.Saifful Izzuan (2009)
This project will cover from the geographical aspect to steam turbine and finally generator set. For geographical aspect, the author learns about hot spot on the earth such as volcanoes, magma flow and also source for hot steam.